Tiragolumab (Anti-TIGIT) in SCLC: Skyscraper-02, a Towering Inferno - Brazel D; Ou SI; Nagasaka M (Lung Cancer: Targets and Therapy, 2023)
Danielle Brazel,1 Sai-Hong Ignatius Ou,1,2 Misako Nagasaka1– 3 1Department of Medicine, University of California Irvine School of Medicine, Orange, CA, USA; 2Chao Family Comprehensive Cancer Center, Orange, CA, USA; 3St. Marianna University School of Medicine, Kawasaki, JapanCorrespondence: Misako Nagasaka, Department of Medicine, University of California Irvine School of Medicine, 101 the City Drive, Orange, CA, USA, Email nagasakm@hs.uci.eduAbstract: Small cell lung cancer (SCLC) is characterized by rapid progression and poor prognosis. Although the phase II CITYSCAPE-02 trial found objective response rate (ORR) and progression-free survival (PFS) of non-small cell lung cancer (NSCLC) patients improved when tiragolumab was added to atezolizumab and chemotherapy, the phase III SKYSCRAPER-02 failed to find PFS or OS benefit in patients with SCLC. Atezolizumab was the first immunotherapy to show survival benefit in extensive SCLC based on the phase III IMpower133 study. Given that immunotherapy has become the standard of care for SCLC patients, further research is needed into ways to augment the immune system to better treat these patients.Keywords: tiragolumab, TIGIT, immunotherapy, small cell lung cancer